(untitled) (Scientific journal of the Fergana State University, 2023)
The article studies the morphogenetic features, the composition of macro- and microelements, the coefficient of biological absorption in medicinal Capparis spinosa in light serozems, and also proved the high demand of macro elements of phosphorus, and microelements of zinc.